[Students in an audio laboratory] (1965)
An instructor sits at the head of a classroom, looking out to a room of students. The instructor's desk has audio technology on it. Behind the instructor a chalkboard reads (in cursive): 'Please sit in the same corresponding position as in our classroom'.